Offer of dental prosthesis in primary care: Expansion and regional differences in Brazil (Revista Contexto & Saúde, 2023)
The objective of the present study was to analyze the expansion of the offer of dental prostheses by the Oral Health Teams (ESB) according to Braziliangeographic regions. The time series study was carried out with secondary data from Module II of the 1st cycle (2011-2012), Module VI of the 2nd cycle(2013-2014) and Module V and VI of the 3rd cycle (2015-2018) of the External Assessment instrument of the Program to Improve Access and Quality of Primary Care (PMAQ-AB). Proportions were compared between Brazilian regions using the Chi-square test, and between years using the Cochran Q test, using the z test adjusted by the Bonferroni method (p